HUBUNGAN PENGETAHUAN DENGAN PERILAKU PENGGUNAAN GULA, GARAM, DAN LEMAK (GGL) DI RUMAH TANGGA KECAMATAN WATES KABUPATEN KULON PROGO - Tri Siswati; Selsafa Nadiroh; Muhamad Primiaji Rialihanto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Consumption of sugar, salt and fat or fat certainly has benefits for the body as long as meet the recommendation. Indonesian Ministry of Health guide the consumption of sugar, salt and oil were 4 tablespoons, 1 teaspoon and 5 tablespoons respectively, namely G4G1L5 in Indonesia. This research was to determine the relationship between maternal knowledge and behavior on sugar, salt and oil consumption. This was cross sectional survey was conducted in Kunlon Progo, Yogyakarta on 2022. Independent variable was knowledge while dependent variabel behavior of using sugar, salt and fat. We use structure questionnaire for investigating knowledge level and the SQ-FFQ form GGL consumption. We implemented chi-squeare to know the association between knowledge and GGL consumption . Result showed that the mean of knowledge was 72,7±8,5 on most on good level (53.3%), while GGL intake were adequate as many as 84.5%, 59.2% ad 76.2% respectively. As conclusion that there is association between knowledge and salt consumption but not correlates forsugar and fat.